PERANCANGAN APLIKASI DATABASE PENJUALAN PADA KERAJINAN SULAM USUS DESA MARGODADI KECAMATAN JATI AGUNG LAMPUNG SELATAN - Arfida, Septilia; Halim, Sabili (Jurnal Teknologi Informasi dan Bisnis Pengabdian Masyarakat Darmajaya, 2015)
Dedication to community activities is one Tridarma lecturers in applying the knowledge and skills to the general public. One of the goals of this service activities are Small and Medium Enterprises (SMEs) in the province of Lampung. Small and Medium Enterprises (SMEs) is a form of small business community based initiatives establishment someone who was instrumental in reducing the unemployment rate in Indonesia so it can contribute greatly to the income of local and regional income Lampung province and even the country. One of them is the SMEs embroidery intestine. Margodadi village is one of the villages that have Sulam SMEs intestine. Villagers who have intestinal embroidery craft SMEs still perform manual processing that uses handwriting on the books that require the processing of sales database. Based on this it is necessary to design a database processing application on SME sales embroidery craft intestine.Key Words: Designing, Data Base, Sulam Intestine